The Sowing Value of Tansy Phacelia (Phacelia Tanacetifolia Benth.) Seeds in the Long-Term Storage (Agricultural Engineering, 2016)
In 2010 the experiment, which aim was to examine the sowing value of tansy phacelia seeds after eight and nine years of storage, was conducted in the laboratory of the Academy of Agrobusiness in Łomża. The experiment clearly demonstrates that the period of storage of tansy phacelia seeds has an essential impact on the changes of basic parameters of the sowing value. Vetrovska variety had the highest seed germinability among the other varieties of tansy phacelia which were stored for 8 years. At the same time this variety had the highest decrease in seed germinability after 9 years of storage. During the 9-year storage Natra variety showed the highest decrease in thousand seeds weight despite the highest value of this parameter among all the tested varieties immediately after yielding. The results; of the experiment allowed for the conclusion that the economic life: cycle of tansy phacelia seeds is 8 years.